The assessment of adolescent female athletes using standing and reactive long jumps - Moresi, M. P.; Bradshaw, E. J.; Greene, D.; Naughton, G. (Sports Biomechanics, 2011)
The aim of this study was to evaluate the reliability of two long jump tasks and their ability to predict 10 m sprint performance in elite adolescent female athletes. Eight junior national-level female track and field athletes completed three standing (SLJ) and reactive long jumps (RLJ) on portable force plates, followed by three 10 m sprints. Intra-class correlation coefficients (ICC) and coefficients of variation (CV) were calculated to examine reliability. Linear regression results identified the best predictor of average and best 10 m sprint time from the jump kinematic and kinetic measures. The ICCs and CVs indicated good reliability for the majority of kinetic measures however, better reliability was reported for the SLJ. The SLJ was a good predictor of best and average 10 m sprint time, with average horizontal power the best predictor of performance (best; R 2 = 0.751, p = 0.003, Standard Error of Estimate (SEE)% = 2.2 average; R 2 = 0.708, p = 0.005, SEE% = 2.5).